Blue native protein electrophoresis for studies of mouse polyomavirus morphogenesis and interactions between the major capsid protein VP1 and cellular proteins - Horníková, Lenka; Man, Petr; Forstová, Jitka (Journal of virological methods, 2011)
Morphogenesis of the mouse polyomavirus virion is a complex and not yet well understood process. Nuclear lysates of infected cells and cells transiently producing the major capsid protein (VP1) of the mouse polyomavirus and whole-cell lysates were separated by blue native polyacrylamide gel electrophoresis (BN-PAGE) to characterize the participation of cellular proteins in virion precursor complexes. Several VP1-specific complexes were found by immunostaining with the anti-VP1 antibody. Some of these complexes contained proteins from the heat shock protein 70 family. The BN-PAGE was found to be a useful tool for the identification of protein complexes by immunostaining of separated cell lysates. However, whole-cell lysates and lysates of isolated nuclei of cells infected with polyomavirus appeared to be too complex for BN-PAGE separation followed by mass spectrometry. No distinct bands specific for cells infected with polyomavirus were detected by Coomassie blue stained gels, hence this method is not suitable for the discovery of new cellular proteins participating in virion assembly. Nevertheless, BN-PAGE can be valuable for the analyses of different types of complexes formed by proteins after their enrichment or isolation by affinity chromatography.
Keywords: Viral Proteins; mapování interakce mezi proteiny; virové plášťové proteiny; chromatografie afinitní; virové proteiny; Capsid Proteins; Polyomavirus; Host-Pathogen Interactions; interakce hostitele a patogenu; Chromatography, Affinity; Mass Spectrometry; vazba proteinů; proteom; Proteome; Animals; hmotnostní spektrometrie; myši; Mice; zvířata; Electrophoresis, Polyacrylamide Gel; Protein Binding; Protein Interaction Mapping; elektroforéza v polyakrylamidovém gelu